Overview of the Engagement Process to Develop the Future of Cancer Impact (FOCI) Report in Alberta: The Power of Collective Action - Anna Pujadas Botey; Tara R. Bond; Eliya Farah; Chantelle Carbonell; Stacey Dyck; Angela Estey; Douglas A. Stewart; Darren R. Brenner; Paula J. Robson (Current Oncology, 2024)
This commentary provides a detailed overview of the extensive stakeholder engagement efforts critical to the development of the Future of Cancer Impact (FOCI) in Alberta report. The overarching aim of the FOCI report was to support informed and strategic discussions and actions that will help key stakeholders in the province prepare for a future with increasing cancer incidence and survival. Employing a comprehensive approach and a diverse range of engagement activities, insights from a wide spectrum of stakeholders were gathered and subsequently used to shape the content of the report. This inclusive process ensured broad representation of perspectives, contributing to a deeper understanding of the complexities in cancer care. The outcome is a robust, consensus-driven report with recommendations set to drive significant transformations within the healthcare system. These efforts highlight the critical role of extensive, inclusive, and collaborative engagement in shaping healthcare initiatives and advancing discussions crucial for the future of cancer care in Alberta.